Ответ:
-27,4
Пошаговое объяснение:
5,43+(-12,6)+(-2,6)+(-7,8)+(-3,4)+(-6,43)=
=5,43 - 12,6 - 2,6 - 7,8 - 3,4 - 6,43 = -27,4.
5,43 + х + (-2,6) + (-7,8) + у + (-6,43) =
5,43 + х - 2,6 - 7,8 + у - 6,43 = -11,4 + х + у
х = -12,6; у = -3,4
-11,4 + х + у = -11,4 + (-12,6) + (-3,4) = -11,4 - 12,6 - 3,4 = -27,4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-27,4
Пошаговое объяснение:
5,43+(-12,6)+(-2,6)+(-7,8)+(-3,4)+(-6,43)=
=5,43 - 12,6 - 2,6 - 7,8 - 3,4 - 6,43 = -27,4.
Ответ:
-27,4
Пошаговое объяснение:
5,43 + х + (-2,6) + (-7,8) + у + (-6,43) =
5,43 + х - 2,6 - 7,8 + у - 6,43 = -11,4 + х + у
х = -12,6; у = -3,4
-11,4 + х + у = -11,4 + (-12,6) + (-3,4) = -11,4 - 12,6 - 3,4 = -27,4